Learning through assessment An approach towards self-directed learning - Lubbe, Anitia (NWU Self-Directed Learning Series, 2021)
This book aims to contribute to the discourse of learning through assessment within a self-directed learning environment. It adds to the scholarship of assessment and self-directed learning within a face-to-face and online learning environment. As part of the NWU Self-Directed Learning Book Series, this book is devoted to scholarship in the field of self-directed learning, focusing on ongoing and envisaged assessment practices for self-directed learning through which learning within the 21st century can take place. This book acknowledges and emphasises the role of assessment as a pedagogical tool to foster self-directed learning during face-to-face and online learning situations. The way in which higher education conceptualises teaching, learning and assessment has been inevitably changed due to the COVID- 19 pandemic, and now more than ever we need learners to be self-directed in their learning. Assessment plays a key role in learning and, therefore, we have to identify innovative ways in which learning can be assessed, and which are likely to become the new norm even after the pandemic has been brought under control. The goal of this book, consisting of original research, is to assist with the paradigm shift regarding the purpose of assessment, as well as providing new ideas on assessment strategies, methods and tools appropriate to foster self-directed learning in all modes of delivery.